Detetives de verdade?: a incerteza em True Detective - Felipe Luiz da Silveira Borges (2017)
This work aims to reflect on the lane dimension in the crime fiction from its main materialization: the trace. It emerges as a fundamental point for thoughts about the narrative and epistemological implications of a whole tradition and a phenomenon in particular: the television series True Detective. For this, we call several other texts, with emphasis on the TV shows, but also revisiting literary and cinematographic productions. From a mapping that unfolds throughout the dissertation, we insert and highlight True Detective in the history of crime fiction, observing continuities and ruptures that evidence a crisis of modern knowledge. In problematizing the positivist model, the trace predicted by the indiciary paradigm inserts the figure of the subject in the way of knowing the world, a factor that allows us to think the figure of the detective in this work. In True Detective, the investigator is a problematic and flawed character, features that inevitably make up his work and his worldview. His difficultyin dealing with the vestiges evidences the impossibility of reaching a single truth, in a storytelling marked by versions that accumulate and contradict themselves, summoning the viewer himself to propose his interpretation on the clues left in the narrative. Against this background, we analyze crime fiction and True Detective in the way they reconfigure the modern view of facing knowledge, which seems to collapse in contemporaneity.